Mosque-Based Community Empowerment: A Case Study of Muhammadiyah Mosques in Gowa Regency, South Sulawesi, Indonesia - Andi Zulfikar Busri; Agusdiwana Suarni; Sri Wahyuni (www.amertainstitute.com, 2024)
The mosque is the largest place of worship among the five religions practiced by the Indonesian people, especially in South Sulawesi. The mosque is one of the most important institutions in the Islamic community and plays a significant role in daily life. Data from the SIMAS of the Ministry of Religious Affairs recorded 12,867 mosques in South Sulawesi.The type of research used is a Qualitative Approach. Therefore, the research results show that based on the information provided, the economic empowerment programs for the community conducted or planned in several mosques include the collection and distribution of zakat given to those in need, especially during the fasting month, and the mosques provide small loans to the community to assist them in economic activities.The mosque also strives to have a greater positive impact on the welfare of the community and the overall progress of the mosque.